PENGELOLAAN GURU DALAM RANGKA PENDAYAGUNAAN SUMBER DAYA MANUSIA SECARA OPTIMAL (Studi Evaluatif di Madarasah Aliyah Negeri 2 Padang) - Sakban, Sakban (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The problem in this research is that the management of teachers and staff in order to optimize human resource utilization at Madrasah Aliyah Negeri 2 Padang has not clearly seen the management carried out by the school principal. This study aims to determine the achievement of managing teachers and staff in order to optimize human resource utilization. The purpose of this research is to enrich the scientific paradigm in the field of Islamic Education Management, especially the study of the managerial behavior of madrasah principals. The research approach used in this research is descriptive qualitative research with data collection techniques also carried out through observation, in-depth interviews and documentation. The results of this study indicate that the management of teachers and staff in the context of optimally utilizing human resources has been implemented, but in the development of technological advances, training is still needed that can increase the professional ability of teachers who are related to their fields.